µJSON, a lightweight compression scheme for embedded GNSS data transmission on IoT nodes - Correia, S.; Perez, R.; Matos-Carvalho, J.; Valderi Leithardt (5th Conference on Cloud and Internet of Things, CIoT 2022, 2022)
Embedded computing is a sector in strong growth, driven by the increasing offer in the internet of things. Since position information is typically one of the intrinsic features of a sensory platform, the present work considers and analyzes the embedded lossless compression of localization data. A structural data scheme is proposed based on the number of occurrences of the independent coordinate components, named as ?JSON. It is shown that, when considering a low-level language implementation on an embedded processor acquiring GNSS data, the proposed schema implies lower compression rates than its counterparts. An embedded test-bench platform is assembled, and several real case scenarios are considered for effectiveness and validation purposes.